2004
DOI: 10.1111/j.1475-097x.2004.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hypertension and left ventricular function in end stage renal failure: a pilot study using cardiovascular magnetic resonance imaging

Abstract: Cardiovascular disease is the principal cause of mortality in patients with renal failure. Left ventricular (LV) abnormalities are adverse prognostic indicators for cardiovascular outcome. The aim of this study was to use cardiac magnetic resonance scanning (CMR) to define LV functional abnormalities in haemodialysis (HD) patients and clarify the determinants of blood pressure (BP) and the effect of anaemia in this population. We studied 44 HD patients and 11 controls with CMR performed following dialysis. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
(40 reference statements)
2
31
1
Order By: Relevance
“…This contrasts with other published data that demonstrated a strong correlation between LVM and anemia (11,28), and the most likely explanation is the higher values and narrower range in our cohort (mean hemoglobin 11.3 g/dl; SD 1.3) compared with other studies.…”
Section: Anemia As a Predictor Of Lvmi?contrasting
confidence: 55%
See 2 more Smart Citations
“…This contrasts with other published data that demonstrated a strong correlation between LVM and anemia (11,28), and the most likely explanation is the higher values and narrower range in our cohort (mean hemoglobin 11.3 g/dl; SD 1.3) compared with other studies.…”
Section: Anemia As a Predictor Of Lvmi?contrasting
confidence: 55%
“…Since 2002 (10,11,13), we have used CMR as part of the standard assessment of patients for renal transplantation. The renal transplant unit at the Western Infirmary (Glasgow, Scotland, UK) provides transplant services to a population of 2.8 million people in the west of Scotland.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no significant association between these aforementioned risk factors and the severity of myocardial stunning, possibly because cardiorenal performance is influenced by a number of humoral and genetic factors (26) that act collectively to exert an effect but in isolation, particularly in pediatrics, are too small to be detectable from our sample size. The major determinant of intradialytic BP is cardiac output and end diastolic volume (27), but clearly regional LV function is important as evidenced by reports of reduced hemodynamic stability in patients developing myocardial stunning despite below average UF volumes (13). Shoji et al (28) found BP reduction during dialysis and not hypertension in adult HD patients as a factor that influenced survival negatively.…”
Section: Discussionmentioning
confidence: 99%
“…CMR was performed using a 1.5-Tesla MRI scanner (Sonata, Siemens, Erlangan, Germany) with LV mass and function assessed as described previously (9). In hemodialysis patients, CMR was consistently performed 24 h after the end of the last dialysis session.…”
Section: Cmr Technique and Analysismentioning
confidence: 99%